Thermoforming of heart valve mold for reconstruction of a replacement heart valve - Lee, Samuel Binhao (2017)
Artificial heart valve for replacement of a diseased valve has been well established and commercially available. The Single Point Attached Commissure (SPAC) approach to reconstruct a replacement aortic valve was developed and patented by Prof Yeo Joon Hock and Dr Wolfgang Goetz in 2008, by using a pair of valve mold and pericardium from the patient. This SPAC valve mold was 3D printed. For animal trials and initial clinical investigation, 3D printing of the valve mold is cost effectively. In the longer term, this project aims to provide a safe and cost effective method of reconstructing a replacement aortic valve with plastic SPAC valve mold. The plastic valve mold can be disposed after it is used for the reconstruction process. The objective on this Final Year Project (FYP) is to explore viable approach to produce the plastic valve mold. Two possible methods were considered; (i) Plastic Injection Molding (ii) Thermo-Forming Plastic injection mold involves an expensive and complex process to fabricate the injection mold. The thermoforming approach is comparatively simpler that requires heating of a plastic sheet and formed over a mold with suction pressure. The scope of work in this FYP involves designing of the mold for thermoforming, material selection for 3D printing and fabricating the thermoformed valve mold. The SPAC valve mold (size 25) was used in this project to design the mold for thermoforming. High temperature resin that can withstand temperature of up to 289°C was selected for 3D printing. It was found that the heart valve mold can be thermoformed using this approach. Compared to injection molding, this in-house design of thermoforming of SPAC valve mold yield significant cost savings of about $45,000 - $50,000.